Empowering 21st-Century Skills through Ethno-PjBL: The Case of ‘Geplak’ in Science Education - Rahmat, Shafira Ramadhina; Tyas, Rizki Arumning; Wilujeng, Insih; Hastuti, Purwanti Widhy; Susilowati (SEMESTA: Journal of Science Education and Teaching, 2025)
Developing 21st-century skills—such as critical thinking and communication—is essential to prepare students for real-world challenges, yet these skills remain underdeveloped in many science classrooms. This study investigates the effect of the Project-Based Learning (PjBL) model integrated with ethnoscience content based on the traditional food "Geplak" on students’ critical thinking and communication skills in the context of science education. It also examines whether significant differences exist between students taught using ethnoscience-based PjBL and those taught using the Discovery Learning model on the topic of food additives. A quasi-experimental design was employed with eighth-grade students, divided into an experimental group and a control group. The experimental group received learning through the PjBL model with ethnoscientific integration, while the control group followed the Discovery Learning model. Data were collected through pretest-posttest assessments on critical thinking, communication skill questionnaires, and observation sheets. MANOVA and effect size analyses revealed that the PjBL model significantly enhanced students’ critical thinking and communication abilities. The findings suggest that integrating local cultural content such as traditional food into science learning can meaningfully contribute to the development of essential 21st-century skills.